DELIVERY ROUTE OPTIMIZATIONMODEL - Raffo Lecca, Eduardo (2005)
The article proposes one model for the delivery problem. We decided to make a model of mathematic programming that can answer questions on how to realize the delivery of articles from one point named warehouse, to destiny places; looking to minimizing costs when translating or transporting goods or articles. The results obtained for the model, to fulfill an average demand of 80 boxes to deliver, require of 5 small lorries for an optimal delivery; it means only 5 routes or tours are needed to fulfill all delivery to customers.